IMPROVING ENGLISH VOCABULARY MASTERY USING JUMBLED LETTERS GAME - Zahara, Evita; Salam, Urai; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
This Classroom Action Research is conducted to improve students’ vocabulary mastery through Jumbled Letters Game. The subjects of this research were 35 class VIIA students of SMPN 1 Kembayan, Sanggau in academic year 2013/2014. To collect the data of research, the writer and research collaborator employed observation checklist to know students’ progress in learning English vocabulary within two cycles. Field notes were also used to monitor the teacher and students’ performance. The result of data analysis showed that class VIIA students got their progress in mastering vocabulary. In the first cycle, the students’ mean score of vocabulary mastery was only 58.57 and categorized as poor. By doing all the steps of classroom action research, the process of teaching and learning was evaluated and modified, including providing clues for the students during playing the game. Then in the second cycle, the mean score of the students was improved to 72 which categorized as good. It showed that there was an improvement of the students’ English vocabulary mastery after applying the jumbled letters game during teaching learning activity. Keyword: vocabulary mastery, jumbled letters game, improving Abstrak: Penelitian Tindakan Kelas ini dilakukan untuk meningkatkan penguasaan kosa kata siswa melalui Permainan Huruf Bercampur. Subyek penelitian ini adalah 35 siswa kelas VIIA dari SMPN 1 Kembayan, Sanggau tahun ajaran 2013/2014. Untuk pengumpulan data penelitian, penulis dan kolaborator penelitian menggunakan checklist observasi untuk mengetahui kemajuan siswa dalam mempelajari kosa kata Bahasa Inggris dalam dua siklus. Catatan lapangan juga digunakan untuk melihat performa guru dan siswa. Hasil analisis data menunjukkan bahwa siswa kelas VIIA mengalami kemajuan dalam penguasaan kosa kata. Dalam siklus pertama, nilai rata-rata siswa hanya 58.57 dan kategorinya buruk. Dengan melakukan semua langkah-langkah dalam penelitian tindakan kelas, proses belajar mengajar dievaluasi dan dimodifikasi, termasuk menambahkan petunjuk bagi siswa selama bermain. Kemudian di siklus kedua, nilai rata-rata siswa meningkat menjadi 72 dan kategorinya baik. Ini menunjukkan bahwa terdapat peningkatan dalam penguasaan kosa kata Bahasa Inggris oleh siswa setelah menerapkan Permainan Huruf Bercampur selama aktifitas belajar mengajar. Kata kunci: penguasaan kosa kata, permainan huruf bercampur, meningkatkan